Medical Chemistry: Theory and laboratory exercises for the first - Єльцов, С.В.; Водолазька, Н.О.; Ворошилова, Ю.В.; Василець, Г.Ю.; Корсун, О.М.; Кравченко, О.А. (ХНУ імені В. Н. Каразіна, 2013)
Manual includes theory and laboratory exercises for the first module of course “Medical Chemistry” for students of medical specialities of universities. It consists of material on se- lected topics: chemical elements and periodic table of the elements, chemical bonding and complex formation, electrolytic dissociation, acidity and acid-base equilibria in solutions, colligative properties of solutions.
Keywords: Medical Chemistry